Monitoring the external load of counter-attack drills in youth soccer using GPS devices: The influence of time pressure and numerical superiority on players` responses - Rochael, M.; Praça, G. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study aimed to analyse the impact of including time pressure on players` physical responses related to distance covered at different speed zones and accelerations performed during balanced and unbalanced small-sided soccer games. Forty-four U-17 athletes from elite clubs were recruited. Players engaged in four formats of small-sided games: 4vs4 (with and without time pressure) and 5vs4 (with and without time pressure, plus additional floaters). Physical responses were monitored through Global Positioning System devices. A MANOVA compared data at a level of significance of 5%. There were no differences between with and without time pressure formats for both distances and accelerations. However, games played in numerically balanced conditions elicited greater physical responses regarding distance covered and distances covered in different speed zones. Specifically, the numerically balanced condition showed higher distances in the higher speed zones than the floater condition, which showed higher values in the lowest speed zone than the 4vs4 condition. This study concluded that adopting the time pressure to represent counter-attack situations does not change the players` physical responses; adopting numerical superiority without adjusting the pitch size will reduce the physical responses.